Efektivitas Konten Media Sosial Tiktok Pada Akun @Eva Alicia Dalam Meningkatkan Aktualisasi Diri Pada Generasi Z Di Prodi KPI UINSU STAMBUK 2021 - Natasya Natasya; Syukur Kholil (STAI Bumi Silampari, 2025)
This study aims to analyze the effectiveness of TikTok social media content on the @eva.alicia account in increasing self-actualization in generation Z, especially students of the Islamic Communication and Broadcasting Study Program (KPI) of the State Islamic University of North Sumatra (UINSU) stambuk 2021. Self-actualization is one of the highest needs in the hierarchy of human needs according to Abraham Maslow, which reflects the full realization of the individual's potential. In today's digital era, social media is one of the dominant means of self-actualization among generation Z. TikTok as a short video-based platform has become a very popular medium of self-expression and development. The @eva.alicia account, which consistently presents motivational, self-improvement, and self-love content, is considered to be able to have a positive influence on the behavior and way of thinking of its audience. The research method used was quantitative descriptive with data collection techniques through the distribution of questionnaires to 70 UINSU KPI student respondents. The results of the study showed that most of the respondents felt encouraged to recognize their potential, improve their quality, and be more confident in expressing themselves in public spaces after consuming content from the account. In addition, respondents also showed increased awareness of the importance of mental health, skill development, and forming a positive self-image.